Increased Risk of Dementia When Spouse Has Dementia? The Cache County Study - Norton, Maria C. (2010)
OBJECTIVES: Chronic psychosocial stress in caregivers can lead to adverse health outcomes including depression, anxiety, and cognitive decline. We examined the effects of having a spouse with dementia on one’s own risk for incident dementia. DESIGN: Population-based study of incident dementia in spouses of persons with dementia. SETTING: Rural county in northern Utah. PARTICIPANTS: 2,442 subjects (1,221 married couples) aged 65 and older. MEASUREMENTS: Incident dementia was diagnosed in 255 subjects, with onset defined as age when subject met DSM-III-R criteria for dementia. Cox proportional hazards regression tested the effect of time-dependent exposure to dementia in one’s spouse, adjusted for potential confounders. RESULTS: A subject whose spouse experienced incident dementia onset had a six-fold increase in the hazard for incident dementia compared to subjects whose spouses were dementia free [Hazard Rate Ratio (HRR)=6.0, 95% CI: 2.2–16.2 (p<.001)]. In sex-specific analyses, husbands had higher risks (HRR=11.9, 95% CI: 1.7–85.5, p=.014) compared to wives (HRR=3.7, 95% CI: 1.2–11.6, p=.028). CONCLUSION: The chronic and often severe stress associated with dementia caregiving may exert substantial risk for the development of dementia in spouse caregivers. Additional (not mutually exclusive) explanations for findings are discussed.